Rohingya Crisis: An Added Challenge in Neurosurgical Arena of Chattogram Medical College Hospital (Bangladesh Journal of Neurosurgery, 2020)
Rohingya are the group of people who has an specific ethnic, linguistic and religious group lived in the former Arakan state, renamed as Rakhain state of Myanmar. These people are homeless, stateless and disowned by their own government. Chattogram Medical College Hospital is the only tertiary level government hospital nearest to the Rohingya camp where Rohingya patients are referred from local health care providers. On a cross sectional observational demographic study conducted in the Department of Neurosurgery, CMCH revealed that, total number of admitted patient in CMCH is 757 among which 137 (18.09%) patient was admitted in Department of Neurosurgery since the Rohingya citizens are forcibly displaced from their land. Traumatic brain injury (31) , spinal injury (22) and gun shot wound (3) are the most common presentation as a result of ethnic cleansing. But lack of primary health care support, proper health education leads to development of hydrocephalus (8), meningocele (8), meningomyelocele (1) in children and delayed presentation of ICSOL (15) and Spinal SOL (2) are also observed among the admitted patients. 67 (48.90%) patients were treated conservatively and 70 (51.09%) patients are treated operatively. Despite the existing over crowded patients from the Chattogram Division, these Rohingya patients made an added challenge to the Department of Neurosurgery. Proper strategic plan should be carried out for the management of neurosurgical condition for decreasing mortality and morbidity and thus support humanity above all.Bang. J Neurosurgery 2020; 9(2): 111-116